Eliminating oxygen releasing of Li-rich layered cathodes by tuning the distribution of superlattice domain. (July 2022) - Wei, Zhining; Shi, Zhepu; Wen, Xiaohui; Li, Xiao; Qiu, Bao; Gu, Qingwen; Sun, Jie; Han, Yingying; Luo, Hao; Guo, Haocheng; Xia, Yonggao; Yin, Chong; et al.
Abstract: Li-rich layered cathodes suffer from oxygen releasing with the undesired rapid performance decay at subsequent cycles. Herein, we propose a strategy on tuning the distribution of Li2 MnO3 -like domains to eliminate oxygen evolution. The distribution regulation is turned by the Li + concentration in the early synthesizing stage, which is caused by the altered participation of Co 3+ in the Li2 MnO3 -like configuration. The detailed local structural evolution is revealed by corresponding extended X-ray absorption fine structures. As calculated and simulated from synchrotron X-ray diffraction results and FAULTS program, the Li2 MnO3 -like domain can be well-dispersed in the lattice. No oxygen release with little carbon dioxide gas is detected by operando differential electrochemical mass spectrometry. The dispersed Li2 MnO3 -like microstructures can withstand more stress induced by structural distortion as confirmed by operando X-ray diffraction. The as-fabricated 10.5 Ah pouch cell with Li metal anode exhibits a specific energy density of 504 Wh kg −1 on the basis of cell mass. This work provides an effective approach to suppress oxygen releasing for high-energy-density lithium secondary batteries. Graphical abstract: Image 1 Highlights: The Li/TM ratio is changed to facilitate the intrusion of Co into LiMn6 superlattice. The modified material achieves no lattice oxygen releasing. A 10.5 Ah pouch cell delivers a high specific energy of 504 Wh/kg at 0.1C. Practically feasible cathodes for high-energy-density commercial applications.